Protestar por los derechos, el derecho a protestar. Una lectura desde las audiencias (2013)
Social protests, conducted as collective actions for which some rights are recognized, are often amplified by the media, to whose rules, nevertheless, they must subordinate. Also, at the reception, multiple variables are set to play and give closure to the televised discourse in different ways. This paper focuses on the moment of consumption of televised social protests, particularly in relation to the rights at stake, the mediatized rights and the way audiences read them.